Deep sub-wavelength broadband metasurface with micro-perforated panels and extended-neck Helmholtz resonators - Bennett, Gareth (My University, 2025)
This study develops, fabricates, and characterizes a deep sub-wavelength broadband acoustic metasurface for noise absorption. The metasurface is composed of micro-perforated panels coupled with extended-neck Helmholtz resonators, forming a unit absorber referred to as an MHA. Experimental results demonstrate that a 48 mm deep MHA achieves near-perfect sound absorption (>97%) at 150 Hz. This performance is realized with a sub-wavelength thickness of only 1/48 of the operating wavelength and a volume-normalized wavelength ratio of 1/54. Additionally, the MHA exhibits a half-absorption bandwidth of 48 Hz. To broaden the sound absorption bandwidth while keeping the total area constant and to further reduce the total thickness, a configuration integrating three Compact MHA units (CMHA) is proposed. Experimental results demonstrate that the CMHA achieves an average sound absorption coefficient (SAC) exceeding 0.74 in the 300±500 Hz range with an overall thickness of only 27.5 mm, and an SAC>0.88 in the 543±945 Hz range with a reduced thickness of 26.2 mm . Experimental results compare well with theoretical and numerical predictions, highlighting the potential of the proposed design for practical noise control applications.
PUBLISHED
Keywords: acoustic metasurface, deep sub-wavelength, broadband, sound absorption, micro-perforated panel, Helmholtz resonator